Inside the Disposal Box: A Study on Biomedical Waste Awareness Among Aspiring Dental Professionals - Tamboli, Sabiha S; Tamboli, Faraz (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Biomedical waste management across India has become a growing concern for dentists. This study investigates biomedical waste management knowledge in the context of dental education. The aim of this study is to determine the knowledge, compliance and understanding levels of dental students regarding the processing and disposal of biomedical waste. Methods: This study was conducted among students and interns of a rural dental college in Maharashtra, India. A pre-designed survey was administered to dental students in various academic years. Investigations include waste classification, segregation, disposal technologies, safety procedures, and environmental impacts associated with biomedical waste. Results: A total of 150 students participated. The male/female ratio is 1:1.31. On average, 88% and 12% of students have correct and incorrect information about biomedical waste. Conclusion: The results of this study can form the basis for the development of educational strategies and interventions to raise awareness and ensure responsible biomedical waste management in medical education, dentistry, and medical facilities. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 198-202